REPORTING OF CORPORATE SOCIAL RESPONSIBILITY IN SMES SECTOR IN POLAND - Kotowska, B.; Martyniuk, T. («Вісник ЖДТУ»: Економіка, управління та адміністрування, 2015)
In Poland and worldwide, corporate social responsibility has a growing interest of managers, business institutions, investors and the government. Thus, it becomes progressively determinant of corporate governance and priority in building a comprehensive development strategy. CSR is used by large companies. However, this does not mean that SMEs sector companies operate less responsible than large one. Each enterprise, regardless of size, operates in a specific social surroundings and market environment, which are affected by different groups of stakeholders. They may affect enterprise reinforcing effect on - contribute to its success or failure. It is therefore important that the managers should be able to identify social groups in the enterprise and its environment and respect their claims, needs, rights and expectations. The aim of this paper is to show the application of CSR by micro, small and medium-sized enterprises in Poland and the manner of result presentation. This article lists tools of corporate social responsibility, examples of practices and research results in the SMEs sector in Poland.